Morphological variations of an invasive cyprinid fish (Carassius gibelio) in lentic and lotic environments inferred from the body, otolith, and scale shapes - Durrani, Omerhan; Atessahin, Tuncay; Eroglu, Mucahit; Dusukcan, Mustafa (Wiley, 2023)
This study investigated the morphological variation of gibel carp Carassius gibelio collected from various water bodies in Turkiye. The fish samples were obtained from three dams (Karacaoren-1, Karakaya, and Keban), two natural lakes (Beysehir and Sugla), and a river (the Tigris River). The dimorphism in body shape was examined with geometric morphometrics, while elliptic Fourier analysis and shape indices were used to describe the variation in sagittae otoliths (hereafter otoliths) and scale shapes. The body of C. gibelio revealed higher variations, particularly in the body depth, snout length, caudal fin, and caudal peduncle, among different stations. Geometric morphometric analysis determined a streamlined body shape of C. gibelio in the Tigris River compared to other stations, while C. gibelio from the natural lakes had a deeper body shape. The body of C. gibelio exhibited a significant homogenous shape between the Beysehir and Sugla lakes, providing the lowest Procrustes distance. The elliptic Fourier analysis revealed that the otolith shape varied significantly between all stations. However, the scale shape was remarkably similar among nearby areas such as Karacaoren dam, Sugla, and Beysehir lakes. These results evinced high degree of intra-population morphological variation in C. gibelio in response to prevailing environmental conditions that probably facilitate their successful establishment in a novel environment.
Keywords: Cypriniformes; ecosystem; elliptical fourier analysis; multivariate analysis; phenotypic plasticity